Aplicación de una metodología de innovación en sistemas empresariales a una institución prestadora de salud (2020)
The study case is a healthcare provider institution specialized in ophthalmology. This company stands out thanks to its diagnostic exams services and the technology it uses. Even though the company is well positioned in its sector, it has several weaknesses in the information technology area. Its main relational database is based on Microsoft Access and it was implemented over ten years ago. Furthermore, its inventory software is a source of complaints from behalf of the workers. This company has several problems, and the objective of this project is to prioritize one and solve it through an innovation methodology for Enterprise Information Systems. This way, the problem that is sought to be solved in this project is: How can a specific pain point, from a healthcare provider company with a strong tradition, be identified and alleviated using an enterprise systems innovation methodology? The methodology to solve this problem is structured in four phases, and includes elements from SCRUM, Human Centered Design and Design Thinking. This methodology is focused in user experience, where the user is studied in detail. As the project is carried out, opinions and comments of the target users are kept in mind for the development of the prototypes. As a consequence, it is observed that the users have a very positive reception of the different proposed prototypes, as well as the final proof of concept.